2022
DOI: 10.1155/2022/4891134
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Being at Risk of Stroke and Its Determinant Factors among Hypertensive Patients in Banyumas, Indonesia

Abstract: Background. The global burden of stroke is still high, particularly in developing countries, with hypertension serving as the main risk factor. The awareness of stroke among hypertensive patients is crucial for stroke prevention. This study was aimed at identifying the awareness of being at risk of stroke and its determinant factors among hypertensive patients in Banyumas, Indonesia. Methods. This was a cross-sectional study conducted in Primary Health Centers (PHCs) in Banyumas Regency, Indonesia, from April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our study result is also similar to most previous international studies that indicated the level of knowledge and the basic understanding of risk factors and warning signs of stroke were inadequate among people with high blood pressure (Bhat et al, 2021; Houessou et al, 2021; Melak et al, 2021). For example, a study conducted in Indonesia found that the majority of patients with high blood pressure in the study were unaware of the risk of stroke (Setyopranoto et al, 2022). In contrast, our result is inconsistent with the studies conducted in Cameroon among the general public, which found high knowledge about stroke risk factors and warning symptoms (Nansseu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study result is also similar to most previous international studies that indicated the level of knowledge and the basic understanding of risk factors and warning signs of stroke were inadequate among people with high blood pressure (Bhat et al, 2021; Houessou et al, 2021; Melak et al, 2021). For example, a study conducted in Indonesia found that the majority of patients with high blood pressure in the study were unaware of the risk of stroke (Setyopranoto et al, 2022). In contrast, our result is inconsistent with the studies conducted in Cameroon among the general public, which found high knowledge about stroke risk factors and warning symptoms (Nansseu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of this study, Rasheed and Adegbenro 8 also documented a low awareness of stroke risk factors in Nigeria following their research. A similar study in Indonesia also reported low level of awareness of the risk factors of stroke 29 . The similarity may be due to shared socio‐demographic factors and health education between the two countries.…”
Section: Discussionmentioning
confidence: 77%
“…A similar study in Indonesia also reported low level of awareness of the risk factors of stroke. 29 The similarity may be due to shared socio‐demographic factors and health education between the two countries. Contrary to this, a higher percentage of individuals had a good level of awareness about the risk factors of stroke after the study in Turkey.…”
Section: Discussionmentioning
confidence: 99%